Young Women’s Attitudes and Behaviors in Treatment and Prevention of UTIs: Are Biomedical Students at an Advantage? - Ivan Jerkovic; Josipa Bukic; Dario Leskur; Ana Seselja Perisin; Doris Rusic; Josko Bozic; Tomislav Zuvela; Sara Vuko; Jonatan Vukovic; Darko Modun (Antibiotics, 2023)
We wanted to investigate whether students who study within biomedical fields (i.e., medicine, pharmacy science) differ from those whose studies are not connected to the biomedical field in terms of their attitudes and behaviors related to urinary tract infections (UTIs). This was a cross-sectional survey-based study conducted among 392 female students, of whom 243 attended a biomedical school and 149 (38.0%) attended a non-biomedical school, using a previously published tool. The survey was distributed as an online link via student representatives at different faculties. Only 22 (5.6%) of women felt that they could not recognize a UTI. A greater proportion of biomedical students wiped front to back, while significantly more non-biomedical students chose cotton underwear and avoided daily sanitary pads compared to biomedical students. As many as 215 (54.8%) women stated that they used cranberry preparations. Biomedical students showed greater awareness about possible resistance to repeated treatment (p = 0.002) and greater knowledge of possible interactions of antibiotics (p < 0.001). This study reveals that young women are confident in recognizing an UTIs, are open to alternative treatments, and would consider UTI management in a pharmacy setting. However, it reveals that there might be gaps in their knowledge regarding antibiotic resistance risks, possible interactions, and efficacy of available preparations, as participants from the group of biomedical students showed greater knowledge and different behaviors.